REVIEW OF DRUG-DRUG INTERACTIONS OF IMMUNOSUPPRESSIVE DRUGS WITHIN KIDNEY TRANSPLANT RECIPIENTS - Jović, Maša; Danković, Katarina; Damnjanović, Ivana; Krstić, Nikola; Mitić, Branka; Stefanović, Nikola (Archives of Pharmacy, 2023)
Drug-drug interactions are frequently observed in kidney transplant recipients due to polypharmacy and the use of immunosuppressive drugs (1). Identifying the interaction of immunosuppressants is of great importance since they can increase the risk of adverse effects (2,3). This study aimed to review the frequency and severity of interactions between immunosuppressants and other prescribed drugs during the first year after kidney transplantation. The research included 99 patients on triple immunosuppressive protocol consisting of tacrolimus, mycophenolate mofetil/mycophenolic acid, and corticosteroid. Drug-drug interactions were identified by three different databases: British National Formulary (BNF), Lexicomp, and Epocrates. The frequency and severity of interactions were determined for each patient during the first post-transplantation year. To facilitate comparison between databases, all interactions were categorized as mild, moderate, or severe. The total number of identified interactions was 130, with 33 BNF (24.24% severe), 67 Lexicomp (without severe), and 108 Epocrates (11.11% severe). The average number of interactions per patient according to the BNF was 2.30±1.59, whereas 1.88±1.10 were mild, 0.23±0.47 moderate, and 0.19±0.67 severe. According to the Lexicomp, the average number of interactions was 7.00±2.36, of which 1.07±0.43 were mild, and 5.93±2.20 moderate. Considering Epocrates the average number of interactions was 12.72±3.82, whereas 3.28±1.66 were mild, 8.04±2.71 moderate, and 1.39±0.98 severe. The findings showed that moderate interactions were the most frequent, which according to the Lexicomp and Epocrates require monitoring and/or modification of therapy. The exploration of various sources regarding drug interactions is necessary due to their identification assessment, but also to optimize immunosuppressive therapy.